Timing of collisional and post-collisional Pan-African Orogeny silicic magmatism in south-central Chad - Shellnutt, J. Gregory; Pham, Ngoc Ha T.; Denyszyn, Steven W.; Yeh, Meng-Wan; Lee, Tung-Yi (Precambrian research, 2017)
[Display omitted] •Silicic rocks of the Guéra Massif range in age from 595±8Ma to 556±7Ma.•Granites located near Lake Fitri are 551±6Ma and 545±6 Ma.•The basement of the Doba Basin is composed of diorite that is 572±0.3Ma.•Collision-related magmatism extends to ∼590Ma in south-central Chad.•Post-collisional magmatism correlates with two crustal relaxation-deformation cycles. Precambrian crust within southern Chad and eastern Cameroon preserves rocks that were remobilized and emplaced during and after the Neoproterozoic (∼650Ma to ∼610Ma) collision between the Congo, São Francisco, West African cratons and the Saharan Metacraton. The Guéra Massif of south-central Chad and granites located near Lake Fitri are inferred to be of Neoproterozoic age but there are no radio-isotopic dates available to confirm their association with the Pan-African Orogeny (Central African Fold Belt). New zircon U/Pb geochronology of granitic rocks from the Guéra Massif, Lake Fitri region and the Doba Basin of the southern Chad yielded weighted-mean 206Pb/238U ages from 595±8Ma to 545±6Ma. The oldest inherited zircons indicate that the Guéra Massif is either built upon Meso- to Paleoproterozoic (1000Ma–1900Ma) continental crust or that pre-Neoproterozoic rocks were the source of the silicic Ediacaran rocks. The identification of ∼590Ma volcanic-arc granites within the Guéra Massif suggest that subduction continued in the eastern regions of Chad after collision had occurred (≥610Ma) in the west (Cameroon). The younger granites (≤570Ma) are post-collisional in nature and are closely linked to deformation cycles recorded in eastern Cameroon after the main continental collision episode between the Congo Craton and the Saharan Metacraton. The post-collisional granites located in the Lake Fitri region likely represent a westward extension of the Guéra Massif as there are temporal and compositional similarities between the granitic rocks. The age and composition of the diorite from the Doba Basin of southern Chad is similar to post-collisional granites from the Central African Fold Belt of Cameroon and implies that the southern boundary of the Saharan Metacraton may be north of the Doba Basin.